PERAN COALITION FOR ORGAN-FAILURE SOLUTIONS (COFS) DALAM PENANGGULANGAN PERDAGANGAN ORGAN DI MESIR (2006-2011) - Khair, Nadiatul; Nizmi, Yusnarida Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study will analyze the role of COFS in overcoming organ trafficking in Egypt year 2006-2011. COFS has an important role for fight against organ trafficking in Egypt. Organ trafficking become a global issue that is a threat to crimes against humanity. Egypt was one of five organ trafficking hotspots in the world. COFS is a non-profit international health and human rights organization with a mission to end organ trafficking and enhance altruistic and deceased organ donation within standardized, transparent, and accountable channels based on social justice and equity.As for the method used in the study is qualitative research methods with explanation analysis methods. Data collection techniques are used library research techniques which utilizes secondary data obtained through library were abstracted from the literature such as books, journals, reports, documents and other materials that support this research.This study shows that in carrying out their role to overcome organ trafficking in Egypt, COFS implement some major programs, there are five programs conducted by COFS. These programs are outreach programs, creating public awareness, conducting research on victims, in cooperation with relevant elements and provide recommendations to the various parties. This program has big impact in the prevention of organ trafficking in Egypt.Keywords: Role, COFS, Egypt, Organ Trafficking